Review of Electric-Carbon Coupling Market Studies： Status，Challenges，and Sustainability Perspectives - ZHU Jizhong, XIE Chuchu, ZHANG Di, LAN Jing, ZHOU Jialin (Dianli jianshe)
In response to global climate change and the urgent need for energy sustainability，governments worldwide have proposed strategic frameworks for carbon emissions reduction and renewable energy development. Consequently，the study of the electric-carbon coupling market has garnered significant attention. This study critically examines the latest policies in both the electric and carbon markets，providing a comprehensive overview of the global carbon market from an international perspective，thereby synthesizing diverse practices across various carbon markets. Subsequently，focusing on the electric-carbon coupling market mechanism，this study extensively investigates carbon emissions in the electricity sector and analyzes the interactive mechanisms between electricity and carbon trading markets. Additionally，it explores collaborative mechanisms across diverse markets and multiple application scenarios. Finally，the challenges and crucial technologies confronting the current electric-carbon coupling market are outlined，offering policy guidance and prospects for sustainable development.